An adenosine kinase inhibitor, ABT-702, inhibits spinal nociceptive transmission by adenosine release via equilibrative nucleoside transporters in rat. (October 2015) - Otsuguro, Ken-ichi; Tomonari, Yuki; Otsuka, Saori; Yamaguchi, Soichiro; Kon, Yasuhiro; Ito, Shigeo
Abstract: Adenosine kinase (AK) inhibitor is a potential candidate for controlling pain, but some AK inhibitors have problems of adverse effects such as motor impairment. ABT-702, a non-nucleoside AK inhibitor, shows analgesic effect in animal models of pain. Here, we investigated the effects of ABT-702 on synaptic transmission via nociceptive and motor reflex pathways in the isolated spinal cord of neonatal rats. The release of adenosine from the spinal cord was measured by HPLC. ABT-702 inhibited slow ventral root potentials (sVRPs) in the nociceptive pathway more potently than monosynaptic reflex potentials (MSRs) in the motor reflex pathway. The inhibitory effects of ABT-702 were mimicked by exogenously applied adenosine, blocked by 8CPT (8-cyclopentyl-1, 3-dipropylxanthine), an adenosine A1 receptor antagonist, and augmented by EHNA (erythro-9-(2-hydroxy-3-nonyl) adenine), an adenosine deaminase (ADA) inhibitor. Equilibrative nucleoside transporter (ENT) inhibitors reversed the effects of ABT-702, but not those of adenosine. ABT-702 released adenosine from the spinal cord, an effect that was also reversed by ENT inhibitors. The ABT-702-facilitated release of adenosine by way of ENTs inhibits nociceptive pathways more potently than motor reflex pathways in the spinal cord via activation of A1 receptors. This feature is expected to lead to good analgesic effects, but, caution may be required for the use of AK inhibitors in the case of ADA dysfunction or a combination with ENT inhibitors. Highlights: ABT-702 inhibits spinal nociceptive pathway. ABT-702 hardly inhibits spinal motor reflex pathway. The effects of ABT-702 are reversed by ENT inhibitors. The effects of ABT-702 are enhanced by ADA inhibitor. Recruitment of adenosine systems by ABT-702 produces analgesic effects.